2006
DOI: 10.1590/s0103-21002006000300008
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbidade e mortalidade de pacientes em início de diálise

Abstract: RESUMOObjetivos: identificar a co-morbidade e causas de mortalidade dos pacientes em início de diálise e analisar se as variáveis pessoais, a comorbidade, os resultados laboratoriais, o número de dias de internação e número de sessões de diálise são fatores de risco para mortalidade. Métodos: foram incluídos no estudo 102 pacientes que iniciaram tratamento dialítico em um hospital universitário. Foi realizado um registro prospectivo de dados pessoais, laboratoriais, de morbidade e mortalidade. Resultados: a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
22

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 4 publications
(4 reference statements)
1
13
1
22
Order By: Relevance
“…In this study, SAH and DM were found to be the prevalent comorbidities, followed by cardiovascular diseases, which is corroborated by other studies (23,24) . Among the studied patient, 55 (56.1%) of them presented SAH, which is evidence of the high prevalence of this disease in patients with renal diseases.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, SAH and DM were found to be the prevalent comorbidities, followed by cardiovascular diseases, which is corroborated by other studies (23,24) . Among the studied patient, 55 (56.1%) of them presented SAH, which is evidence of the high prevalence of this disease in patients with renal diseases.…”
Section: Discussionsupporting
confidence: 91%
“…The use of sterile transparent film is recommended to dress the site of catheter insertion among patients undergoing hemodialysis (4)(5) . The use of transparent film in dressings in central venous catheter for hemodialysis did not protect against infections when compared to normal dressings.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that in the population starting dialysis (n=106), the most common infection site was the blood stream related with the use of central venous catheter, which corresponds to 50% of the infections compared to other sites (4) . Bacteremia is the most severe catheter-related complication and it may evolve to endocarditis, significantly increasing morbidity and mortality of patients undergoing this therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When CRI is diagnosed, a conservative or dialysis treatment should be started as early as possible, otherwise, the complications can lead to death (2) .…”
Section: Introductionmentioning
confidence: 99%